2017
DOI: 10.3832/ifor2223-010
|View full text |Cite
|
Sign up to set email alerts
|

Canopy temperature variability in a tropical rainforest, subtropical evergreen forest, and savanna forest in Southwest China

Abstract: (1-2) Canopy temperature (Tc) measurements with infrared thermometry have been widely used to assess plant water status. Here, we evaluated Tc and its controlling factors in a primary tropical rainforest (TRF), subtropical evergreen broad-leaved forest (STF) and valley savanna forest (SAF) in southwestern China. We found differences between Tc and air temperature (Ta) of as much as 2.2 °C between the dry and wet seasons in the TRF. However, the canopyto-air temperature difference (Tc-Ta) was only 0.3 °C betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Our analysis showed that the Tc of the two sites exhibited clear diurnal and seasonal variation above Ta throughout the day and the year, indicating that the canopy of the studied subtropical forests is typically warmer than ambient air. These warming effects are consistent with previous findings in tropical, subtropical, and temperate natural forests, as well as urban forests [4,6,7,23,25]. By contrast, Asian subtropical forests (2.42-4.58 °C) have a comparable canopy heating effect to ∆T also showed opposite patterns with increasing g c between the two sites (Figure 5b,d).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our analysis showed that the Tc of the two sites exhibited clear diurnal and seasonal variation above Ta throughout the day and the year, indicating that the canopy of the studied subtropical forests is typically warmer than ambient air. These warming effects are consistent with previous findings in tropical, subtropical, and temperate natural forests, as well as urban forests [4,6,7,23,25]. By contrast, Asian subtropical forests (2.42-4.58 °C) have a comparable canopy heating effect to ∆T also showed opposite patterns with increasing g c between the two sites (Figure 5b,d).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the fact that the two sites shared similar climate zones, different temperature and precipitation patterns impacted ∆T and its responses to environmental change. Our results showed that ∆T increased linearly with Rg and decreased nonlinearly with Ws (Figure 5a1-a2,c1-c2), which confirmed the warming effect of radiation and cooling effect of wind on Tc [6,7,23,27]. However, we found that the ∆T at the two sites responded differently to the temperature-influenced variables, such as VPD and g c .…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations